Teaching International Economic Law in Latin America - Gómez-Moreno, Juan Pablo (2026)
This article analyzes the teaching of international economic law in Latin America through a comparative study of thirteen academic programs across six countries in the region. The analysis shows that IEL still occupies a fragmented place within legal curricula, with a strong reliance on foreign scholarship and predominantly traditional teaching methods. It also reveals a limited incorporation of contemporary debates such as digital trade, sustainability, and technological governance.Based on this diagnosis, the article proposes strengthening IEL education through the inclusion of emerging topics, more participatory teaching methods, and the integration of Latin American scholarship and case studies. These measures could contribute to a more contextualized education and to a more informed participation of the region in global economic governance.